2015
DOI: 10.1149/06801.3059ecst
|View full text |Cite
|
Sign up to set email alerts
|

Detailed H2 and CO Electrochemistry for a MEA Model Fueled by Syngas

Abstract: SOFCs can directly oxidize CO in addition to H2, which allows them to be coupled to a gasifier. Many membrane-electrode-assembly (MEA) models neglect CO electrochemistry due to sluggish kinetics and the water-gas-shift reaction, but CO oxidation may be important for high CO-content syngas. The 1D-MEA model presented here incorporates detailed mechanisms for both H2 and CO oxidation, individually fitted to experimental data. These mechanisms are then combined into a single model, which provides a good fit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Conversely, assuming that WGS and SMR are fast reactions, some authors estimate the OCV by substituting the equilibrium partial pressures in Eq. 4 (Stoots et al, 2009;Lee et al, 2015;Jin et al, 2018;Vágner et al, 2019), calculated assuming that both WGS and SMR go to equilibrium at local temperature and pressure, starting from the bulk gas composition. Therefore, using the equilibrium partial pressures allows to indirectly include species like CO and CH 4 in the estimation of the OCV.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, assuming that WGS and SMR are fast reactions, some authors estimate the OCV by substituting the equilibrium partial pressures in Eq. 4 (Stoots et al, 2009;Lee et al, 2015;Jin et al, 2018;Vágner et al, 2019), calculated assuming that both WGS and SMR go to equilibrium at local temperature and pressure, starting from the bulk gas composition. Therefore, using the equilibrium partial pressures allows to indirectly include species like CO and CH 4 in the estimation of the OCV.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the diffusion could be simplified to a single dimension, typically in the flow direction [24][25][26][27] or anode-thickness direction. [28][29][30][31] This captures some of the physics due to 1D gas diffusion and heterogeneous reactions at the solid/gas interfaces, while significantly reducing the computational effort required. Another more widely used approach to reducing the model order is by projection-based mathematical reduction, in which a set of data is mapped into sub-set with certain accuracy.…”
mentioning
confidence: 99%
“…20,22,23 Researchers have found that O spillover to CO on nickel is a more likely pathway than CO spillover to YSZ because CO molecules have a strong affinity to nickel sites. [24][25][26] However, most MEA models represent CO electrooxidation as a global reaction rather than implementing the detailed * Electrochemical Society Student Member.…”
mentioning
confidence: 99%
“…[18][19][20][21] However, understanding the mechanism for CO electro-oxidation is critical to accurately represent syngas mixtures, where CO is present in large enough quantities to contribute to cell current. 20,22,23 Researchers have found that O spillover to CO on nickel is a more likely pathway than CO spillover to YSZ because CO molecules have a strong affinity to nickel sites. [24][25][26] However, most MEA models represent CO electrooxidation as a global reaction rather than implementing the detailed O spillover pathway.…”
mentioning
confidence: 99%